The impact of time management on job performance – An applied study on the employees of the big brother company and electricity – - Etwadi, Ibrahim Mohammed; Abdelall, Adel Hamed (Journal of Economic, Administrative and Legal Sciences, 2021)
The study aimed to identify the effect of time management on job performance in Al-Shuqaiq Water and Electricity Company, and to achieve the objectives of the study, the researcher used the descriptive approach, and the study sample consisted of (82) employees, and the questionnaire was designed as a tool for the study to obtain data. A set of results, the most prominent of which were: the existence of an effect of time management on the performance of the employees of the Shuqaiq Water and Electricity Company, where the arithmetic average was (3.72) and the standard deviation (0.60), and the presence of a positive effect of time utilization among the employees of the Shuqaiq Water and Electricity Company, where the arithmetic average was (4.08). And the standard deviation (0.66), and the presence of a statistically significant effect at a level less than 0.05 between time management and job performance in the brother water and electricity company, and it also showed that the employees of the company realize the importance of completing work on time, and the presence of a statistically significant effect at a level less than 0.05 Between the effect of time use and job performance, the results showed that there are statistically significant differences about the effect of time management on job performance due to the age variable, and there are no statistically significant differences about the effect of time management on The job performance refers to the two variables, academic qualification and years of experience. The study recommended a number of recommendations, the most prominent of which are: the need for the volume of work to be commensurate with the official working hours, as well as the necessity of providing the means and techniques that help workers accomplish the tasks assigned to them efficiently, and the need to educate workers and urge them to set up prior plans for the work that they will undertake.